SASTRA SEBAGAI MEDIA DOKUMENTASI SOSIAL DAN POLITIK DI INDONESIA - Fajar Fikri (PT. Habe Cendekia Utama, 2025)
Literature is a multifaceted and multidimensional concept in Indonesian society. Literature is not merely an aesthetic work but also a social and political document that records the life of society during a particular period or era. This study explores the role of literature in Indonesian socio-political documentation, highlighting its significance as a cultural archive for understanding the nation's historical journey and its role in recording socio-political dynamics. This study uses qualitative research methods with a descriptive, analytical, and objective sociology of literature approach to analyze literary works as socio-political documentation. This research focuses on the structure of literary works, such as plot, characters, and setting, as representations of society's social and political realities. The results show that literature in Indonesia functions dually as both an aesthetic work and an important socio-political document. Literature records social realities such as poverty, injustice, class inequality, and social conflict, and reflects cultural changes and political dynamics from the colonial period to the contemporary era. Literary works serve as alternative accounts that give voice to marginalized groups, critical tools that raise collective consciousness, and rich sources of cultural history.